Morphometric and Genetic Variations of Freshwater Eels (Anguilla spp.) in Poso River, Central Sulawesi: Implications for Conservation Strategies - Samir, Octavianto; Kamal, Mohammad Mukhlis; Kurnia, Rahmat; Larashati, Sekar; Triyanto; Widoretno, Mey Ristanti (BRIN Publishing, 2024)
The freshwater eel, Anguillids, is a valuable nutrition and commodity fish found in various freshwater environments. However, the world's population of Anguillids are declining because of habitat degradation, pollution, and barriers to migration, all of which are prevalent threats to freshwater ecosystems such as the Poso River in Central Sulawesi. Establishing conservation areas is one of the efforts to protect Anguillids and their habitats, which requires information on the anguillids morphometrics and genetics, where high morphometric and genetic variations are indicators of adaptation or evolution of the species to survive environmental changes. Therefore, the study aims to assess the morphometric and genetic variations in the Poso River, Central Sulawesi. Samples were collected along the Poso River in the range of May 2021 and August 2023 . Different fishing gears were used depending on the location and Anguillids’ phase of life. A total of 150 eel samples were used for morphometric analysis, out of which 38 were selected randomly for the genetic one. Genetic diversity analysis was performed based on the Cytochrome c Oxidase I (COI). The study successfully identified three species: A. bicolor, A. celebesensis, and A. marmorata. The key characteristic distinguishing the three species was ADL/TL ratio. Most coefficients of variation of morphometric characters of each species were above 10%, indicating medium to high variation. A total of 11 haplotypes were identified, of which six belong to A. marmorata and five to A. celebesensis. Generally, haplotype diversity was low, ranging from 0.2923 to 0.9333, and nucleotide diversity ranged from 0.0005 to 0.0046. The low genetic diversity observed in this study is likely a result of the migratory nature of Anguillids. Morphometric and genetic variations can support restocking as a conservation strategy to bolster wild populations. However, comprehensive studies must be conducted to understand all aspects impacting Anguillid resources for establishing conservation areas to protecti their populations and habitats.